Environmental processing of galaxies in H i-rich groups. Issue 3 (10th November 2020) - Džudžar, Robert; Kilborn, Virginia; Sweet, Sarah M; Meurer, Gerhardt; Jarrett, T H; Kleiner, Dane
ABSTRACT: We present and explore the resolved atomic hydrogen (H i ) content of 13 H i -rich and late-type dominated groups denoted 'Choirs'. We quantify the H i content of the Choir galaxies with respect to the median of the H i -mass fraction ($f_{\rm{{H {\small I}}}}$ ) of their grandparent H i Parkes All Sky Survey (HIPASS) sample. We find that the H i -mass fraction of the Choir galaxies is dispersed around the HIPASS median in the range $-1.4\le Δ f_{\rm{{H {\small I}}}}[dex]\le$ 0.7, from H i -excess to H i -deficient galaxy regime. The H i -excess/H i -deficient galaxies contain more/less than 2.5 times their expected H i content with respect to the HIPASS median. We show and discuss that the environmental processing in Choirs occurs via tidal stripping and galaxy mergers. Our analysis suggests that tidal stripping contributes to the loss of the H i, while galaxy mergers contribute to the enhancement of the H i . Exploring the mid-infrared properties of Choir galaxies, we find possible environmental processing in only nine Choir galaxies, which indicates that environmental processing is more perceptible in the H i content than the mid-infrared properties. Moreover, we find that environmental processing occurs in Choir groups regardless of their global environment, whether they are in isolation or in proximity to the denser structures, such as cosmic web filaments. We explore possible scenarios of the Choirs evolution, taking into account their H i content, velocity dispersion, crossing time, and their global environment. We conclude that the most likely evolution for the majority of Choir groups is that they will become more compact as their members undergo multiple H i -rich mergers.